PERAN DAN KAPABILITAS TNI DALAM PENGAWASAN LINTAS BATAS : STUDI KASUS KAPABILITAS KOMPI TEMPUR I YONIF 631/ANTANG DI PULAU SEBATIK TAHUN 2010-2011 - Abdullah, M. Si (Han), Mayor Inf Hasan (Jurnal Pertahanan dan Bela Negara, 2018)
This research aims to reveal the role and capability of TNI in monitoring border crossing. Case study was conducted in Sebatik Island, where border situation comprises complex vulnerabilities. However, TNI border security task force in charge succeeded to foil only small number of illegal activities. Research was conducted by qualitative methods based on military capability and border security management concepts, towards documents and interview to selected figures. Result of this study shows that force posture organised in accordance with border security operational standard, will be able to achieve optimum capability in monitoring border crossing if the main role is exercised in activities which are stick with determined strategy, and supported with actual intelligent information. Additional roles related to main tasks of the strategy may emerge in the effects of contributing factors. Whereas in the existence of contributing partners, formal framework is needed to synergize strategies among parties and ensure comprehensive capabilities. Â Keywords : role of TNI, border security, border crossing, capability, monitoring